Refractory hyperaldosteronism in heart failure is associated with plasma renin activity and angiotensinogen polymorphism. Issue 6 (June 2015) - Vergaro, Giuseppe; Fatini, Cinzia; Sticchi, Elena; Vassalle, Cristina; Gensini, Gianfranco; Ripoli, Andrea; Rossignol, Patrick; Passino, Claudio; Emdin, Michele; Abbate, Rosanna
<x xml:space="preserve">Abstract</x> Aims Refractory hyperaldosteronism is frequently observed in heart failure patients on up-to-date treatment, and holds prognostic value. Our aim was to identify which factors, either genetic or nongenetic, are associated with refractory hyperaldosteronism. Methods We enrolled 109 consecutive patients with left ventricular systolic dysfunction [left ventricular ejection fraction (LVEF) 32 ± 10%; 86% males; age 65 ± 13 years (mean ± standard deviation)] on optimized adrenergic and renin-angiotensin-aldosterone system (RAAS) antagonism, undergoing clinical and neuroendocrine characterization, and genotyping for six polymorphisms in key RAAS-regulating genes [angiotensinogen (AGT M235T), angiotensin-converting enzyme (ACE-240A>T and I/D), angiotensin II type I receptor (AGTR1 1166A>C), aldosterone synthase (CYP11B2-344C>T) and renin (REN rs7539596)]. Results Patients with refractory hyperaldosteronism (n = 41, 38%, with plasma concentration >180 ng/l, URL, median 283 ng/l, interquartile range 218–433), when compared with those without (106 ng/l, 74–144; P < 0.001), were not different either for treatment or LVEF, while presented with different AGT M235T genotype distribution (P = 0.047). After adjustment for several humoral, instrumental, functional and therapeutical variables, only plasma renin activity (PRA) (P < 0.001) and potassium (P = 0.027) were independently associated with refractory hyperaldosteronism. Among polymorphisms, only AGT M235T (P = 0.038) was associated with refractory hyperaldosteronism, after adjustment for nongenetic variables. Conclusions In conclusion, refractory hyperaldosteronism in heart failure may be influenced by AGT M235T polymorphism, among RAAS candidate genes, and by PRA, which may represent, respectively, a constitutive (genotype dependent) and a nongenetic (phenotype-dependent) trigger for aldosterone elevation.